2018
DOI: 10.1111/oik.04806
|View full text |Cite
|
Sign up to set email alerts
|

Entrapped carrion increases indirect plant resistance and intra‐guild predation on a sticky tarweed

Abstract: Many plants employ indirect defenses against herbivores; often plants provide a shelter or nutritional resource to predators, increasing predator abundance, and lessening herbivory to the plant. Often, predators on the same plant represent different life stages and different species. In these situations intraguild predation (IGP) may occur and may decrease the efficacy of that defense. Recently, several sticky plants have been found to increase indirect defense by provisioning predatory insects with entrapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Carrion‐removal and ‐addition experiments involving another tarweed species produced similar results; plants with more carrion had fewer herbivores, more predators, and produced more seeds per fruit (LoPresti et al. ). Sticky columbine plants have also been found to attract insects that are nearby (LoPresti et al.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Carrion‐removal and ‐addition experiments involving another tarweed species produced similar results; plants with more carrion had fewer herbivores, more predators, and produced more seeds per fruit (LoPresti et al. ). Sticky columbine plants have also been found to attract insects that are nearby (LoPresti et al.…”
Section: Introductionmentioning
confidence: 83%
“…, Krimmel and Pearse , LoPresti et al. , , Wheeler and Krimmel ). This sticky plant defense syndrome is likely to be more effective in arid and Mediterranean environments where the adhesive materials do not wash off plant surfaces during rainstorms (LoPresti ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scavenging on vertebrate carrion by arthropod decomposers (Benbow et al ., ) and conspecifics by social arthropods (Sun & Zhou, ) is well studied, but facultative scavenging by arthropods on arthropod carrion has been neglected. Facultative scavenging by a diverse group of arthropods has been reported (Lavigne & Pfadt, ; Wheeler, ; Coelho & Hoagland, ; Pierce, ; Foltan et al ., ; Vetter, ) but few studies have assessed the effects of scavenging on individuals and communities (Wilson & Wolkovich, ; Peng et al ., ; LoPresti, ; LoPresti et al ., ; Nelson et al ., ). Our study indicates that scavenging by predators can reduce cannibalism, probably via satiation on arthropod carrion, potentially increasing their abundance.…”
Section: Discussionmentioning
confidence: 98%
“…We found that the presence of P. flava is positively related to the carrion abundance as well as showed by other studies focused on several predators on glandular trichome‐bearing plants (LoPresti et al ., , ). Since the scavenging behavior has been recorded for lynx spiders (Romero et al ., ; and herein), it is possible they take into account the carrion abundance before choosing their host plants.…”
Section: Discussionmentioning
confidence: 99%